Establishing white clover (Trifolium repens) in high pest density regions - Brock, J.L.; Eerens, J.P.J.; Rahman, A.; Wilson, D.J. (New Zealand Plant Protection, 2008)
Four field trials were conducted on commercial dairy farms in Waikato and Manawatu to develop guidelines for reestablishing white clover into vigorous grass pastures Treatments were designed to (1) determine the minimum clover fallow period needed to minimise clover pest populations and (2) identify options for reintroducing white clover Tribenuron proved damaging to grass and results for thifensulfuron were variable Dicamba was effective in removing clover and the length of clover fallow required to remove clover root weevil larvae appeared to be 68 months Glyphosate applied at sowing reduced pasture cover significantly for up to 10 weeks but seedling establishment was improved by 50100 The reintroduction of clover was better in autumn than spring but no treatment resulted in increased long term clover content of the pasture This was due to both poor emergence and survival of clover seedlings facing severe competition from resident well established grass plants